Assess Nurses` Perception Regarding The Use Of Technological Devices In The Critical Care Units At Selected Hospital, Chennai. (Journal of Pharmaceutical Negative Results, 2022)
Background: In conditions of intensive therapy, where the patients treated are in a critical condition, alarms are omnipresent. Nurses, as they spend most of their time with patients, monitoring their condition 24 hours,are particularly exposed to so-called alarm fatigueMethods: A descriptive study design and convenience sample was used and 50 nurses (males and females) who were working in dayshift were included. Three tools were used in the study and analysed statistically. Result: The majority of study participants were female, staff nurses, age < 25.The relation between received training on each technological equipment as total, individual & training on ventilator and perception regarding positive aspects of using technology were statistically significant and there is increased patient risk due to human errors or mechanical faults, increased stress and decreased autonomy was evident on negative effects of equipments.